Promoting Civic Education and State Defense in Increasing Student Participation in the 2024 Elections - Sardjijo Sardjijo (Dinasti International Journal of Economics, Finance & Accounting, 2023)
This study discusses the Role of Civic Education and State Defense in Increasing Student Participation in the 2024 Elections. The purpose of this study is to find out whether the provision of citizenship education and state defense to students plays a role in increasing their participation to participate in the 2024 election party. The object of this study was in adolescents with an age range of 18-23 years. The populationin this study was 90 respondents with a sample of 40 respondents. The research method used is quantitative descriptive, by looking at partial and simultaneous influences. The sample method used is Simple Random Sampling. The research tests carried out are T test, F test and coefficient of determination. The results of this study include: 1) Civic Education has a positive and significant effect in partially increasing student participation in 2024; 2) State Defense Education has a positive and significant effect in increasing student participation in partial 2024 issue; and 3) Civic Education and State Defense have a positive and significant effect in increasing student participation in 2024 simultaneously.